Design and pedagogical implications of a digital learning platform to promote well-being in teacher education. (July 2022) - Moldavan, Alesia Mickle; Edwards-Leis, Christine; Murray, Jennifer
Abstract: Technology can provide enriched learning experiences to engage preservice teachers in self-directed discovery and reflection that promotes well-being. This study examines a digital learning platform designed to educate preservice teachers about the social, physical, emotional, cognitive, and spiritual dimensions of well-being through targeted module activities and community forum discussions. Findings report on the pedagogical design of the platform and its implications for practice on preservice teachers' well-being knowledge across two years of implementation in a teacher education program. Recommendations are shared for how to cultivate and sustain similar platforms to promote well-being for the retention and mental health of teachers. Highlights: Digital learning platform designed in an international collaboration to educate about teacher well-being. Well-being module activities and community forum discussions to facilitate opportunities for an online learning community. Results report on preservice teachers' social, physical, emotional, cognitive, and spiritual dimensions of well-being. Use of digital learning platform positively influences preservice teachers' knowledge of well-being and self-care practices. Recommendations shared for how to cultivate and sustain similar platforms to promote well-being.